MICROCIRCULATION IN PATIENTS WITH POSTTHROMBOPHLEBITIC LYMPHEDEMA OF THE LOWER LIMBS - Umatalie Dilshod .Alievich (Scholar Express Journals, 2024)
Relevance. In diseases of the veins of the lower extremities, they entail secondary changes in the lymphatic system of various severity and volume. Materials and research methods. 92 patients with postthrombophlebitic lymphedema of the lower extremities were examined. In order to determine the state of microcirculation, transcapillary diffusion along the veno-venous gradient was studied. In order to study the resorption and transport capabilities of the lymphatic system, the method of indirect lymphoscintigraphy was used. The level and monitoring of oxygen tension in the tissue were studied. Results. In patients with post-thrombophlebitic lymphedema, a dysfunction of lymphatic drainage was revealed, there are pronounced disorders of microhemo- and lymphocirculation in the affected limb. Conclusions. In patients with post-thrombophlebitic lymphedema, it is necessary to correct not only venous insufficiency but also lymphatic drainage in the complex treatment of this category of patients.
Keywords: post-thrombophlebitic lymphedema of the lower extremities; the state of lymphatic drainage